Archaeology of Standing Buildings: teaching and scientific activities - Andrea Fiorini (Groma, 2016)
This paper will describe the research and teaching project Archaeology of architecture in Romagna where advanced archaeological survey methodologies have been used to investigate the history of monuments and their architectural evolution over time. We selected 46 sites, including 6 ecclesiastical buildings and 40 castles. In the urban landscape the research focused on the church of Santa Croce in Ravenna. The study of the castles of Romagna, and the analysis of building techniques utilised within them, allows us to make observations regarding skills used in the construction of these buildings. Teaching activities have been conducted since 2008 as part of the workshop program of the Department of History, Cultures, and Civilizations. The most recent was carried out in Longana, near Ravenna, in the church of S. Apollinare.